Uncertainty-based key agreement protocol. - Luciano Godoy Fagundes (2007)
This work introduces a new encryption algorithm. The main motivation to the suggested algorithm is to attempt to open new ways and alternative visions that may be eventually integrated into well established cryptography algorithms being used today. When RSA, DES, and several other algorithms are compared, at least a common and central point can be identified; the majority of the known algorithms provides security based on the concept of one-way mathematical functions that are "easy" to be used but "hard" to be broken. The trust on this mathematical statement is fair enough for now; but in a mid-term future, as a foresight act, new technologies can indeed emerge and shake this belief. This work highlights the threat that the Quantum Computers can bring to the current cryptographic algorithms and it proposes a new encryption technique that might be used in conjunction with the current technology. The new algorithm is solely based on low processing power, efficient network communication and uncertainty of the discovery of information.